Selection of Output Elements by Minimum Cost Flow Algorithm - Adamyan, Ruben O.; Markosyan, Stepan E. (Mathematical Problems of Computer Science, 2021)
During the placement stage of VLSI (Very Large Scale of Integration) physical design phase it is needed to take into account the external connections of the placing elements. So later, it is possible to get better result in routing stage. Thus it is required to map external nets of a circuit to its elements in such a way that the maximum number of nets corresponding to an element is minimal. In this article the problem is solved by reducing it to the problem of finding a minimum cost flow of a given value in a network.